AKUNTABILITAS LEMBAGA PEMERINTAH DAERAH DALAM MENCEGAH PATOLOGI BIROKRASI - Hamirul Hamirul (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2019)
In order to improve good governance and clean governance, all local governments must make a report on Government Institution Performance Accountability (LAKIP) using descriptive methods and a kaulitative approach with informants as many as 14 people with the results of the Government Agency Performance Accountability Report on Decision Making in Regional Leaders The Bungo District Inspectorate has gone well even though there are still a number of programs that have not yet been implemented 100% and 2 (two) programs have not been implemented so that some of the pathology of biology related to the Accountability process still occur and to see the performance indicators with the realization of performance indicators set 2017 Annual Performance Determination Documents so that it is more transparent, Efforts to overcome the obstacles of Bungo Regency Inspectorate in creating Performance Reports on Government Agency Performance Accountability to support decision making regional leadership and can prevent bureaucratic pathology, including: Providing training and education to improve the human resource capacity of Bungo Regency Inspectorate personnel; Provide understanding in the form of guidance to the object of examination regarding the importance of internal audit; Strive to improve facilities and infrastructure to support the implementation of basic tasks and functions.